An initiators' Perspective on the continuity of citizens' initiatives in rural areas - Haan, Erzsi Meerstr-de, et al (Rural Sociology)
Against the backdrop of depopulation and the shift toward Big Society, citizens' initiatives in rural areas are believed to be able to mitigate the decline of service provision in rural regions. Consequently, this mitigation requires the continuity of such initiatives. However, so far, we lack an initiators' perspective on the relevance of this continuity and the factors influencing it. From a theoretical standpoint, continuity of citizens' initiatives can be understood at three levels: the participant, group, and initiative levels. Based on empirical data obtained from 157 questionnaires distributed to a variety of initiatives, and using regression analysis, the focus of this paper is twofold. First, how and at which level the initiators understand continuity of an initiative is considered. Second, factors influencing the expected continuity of an initiative are researched. The results reveal that continuity differs from merely being successful and is influenced by other factors as well. Furthermore, continuity on the initiative level$1 (Bthe realization of a certain goal$1 (Bis most prominent in analyzing expected continuity. In conclusion, we explore the roles that citizens' initiatives can be expected to play in service provision and which levels of continuity align with these expectations.- Reproduced s